The missing gun - Lu Chuan (Beijing, China China Film Group Inc.; distributed in the Philippines by MagnaVision, 2002)
A small-town cop wakes up one morning after a wild night of celebration to discover that his gun- a rare, state-issued firearm loaded with three bullets - is missing. While he attempts to retrace his steps from the previous night - his ex-girlfriend turns up dead and the bullet appears to be from his gun!. Now, in order to clear his name and convince the authorities that he's not the killer, he must race againts time to find the gun before the other two bullets find their next victims.
Based on the story "The search for a missing gun" by Fan Yiping.
Jiang Wen, Wu Yujuan, Ning Jing, Liu Xiaoning ; editor, Zhang Yifan ; art director, Lv Dong; director of photography, Xie Zhengyu; writer, Lu Chuan.
VCD.
Keywords: Feature films; Feature films -- China; Foreign films